Availability and advertising of sugar sweetened beverages in South African public primary schools following a voluntary pledge by a major beverage company: a mixed methods study. Issue 1 (1st January 2021) - Erzse, Agnes; Christofides, Nicola; Stacey, Nicholas; Lebard, Kelsey; Foley, Louise; Hofman, Karen
ABSTRACT: Background : Towards the end of the 2017 school year, a prominent beverage company in South Africa pledged to remove their sugar-sweetened beverages (SSBs) and advertisements from primary schools in order to contribute to the realization of a healthy school environment. Objectives : To assess the availability and advertising of the company's beverages in public primary schools in Gauteng province following their voluntary pledge to remove the products, and to explore perceptions of school staff regarding SSB availability in schools and processes related to the implementation of the pledge. Methods : In 2019, we conducted a representative survey of public sector primary (elementary) schools in Gauteng province, South Africa. A random sample of schools was drawn, with schools stratified by whether or not they charge fees. This was a proxy for the socioeconomic status of the locale and student body. At each school, the availability of beverages and presence of advertising or not was assessed by an observational audit tool and differences across fee status assessed by Pearson χ 2 test. Semi-structured interviews were conducted with a purposive sample of school officials. Data from the interviews were coded and thematic analysis conducted. Results : Two years following a voluntary pledge, the company's carbonated SSBs were available for sale in 54% (CI: 45–63%) of schools with tuck shops and advertised in 31% (CI: 25–39%). Qualitative interviews revealed a complex landscape of actors within schools, which, combined with indifference or resistance to the pledge, may have contributed to the continued availability of SSBs. Conclusions : Though we were unable to examine SSB availability before and after the pledge, our findings provide some preliminary evidence that voluntary pledges by commercial entities are not sufficient to remove SSBs and advertisements from schools. Mandatory regulations coupled with in-depth engagement with schools may be an avenue to pursue in the future.